Livestock need investment - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A Chief Veterinary Officer at the Zambian Ministry of Agriculture talks about the importance of preventative health care, and the value of investing in the health of young animals